Exploring task-specific disability on lower extremity strength and quality of life in individuals with patellofemoral pain. - Bhella, Cole; Kim, Sungwan; Mangum, L. Colby; Bazett-Jones, David M.; Boling, Michelle C.; Toland, Michael D.; DiStefano, Lindsay J.; Glaviano, Neal R. (Disability & Rehabilitation, 2026)
Purpose: Compare frequently reported exacerbating tasks in individuals with patellofemoral pain (PFP) to the Anterior Knee Pain Scale (AKPS), Knee Injury and Osteoarthritis Outcome Score-Patellofemoral (KOOS-PF) subscale, and PFP consensus statement. Additionally, we examined differences in lower extremity strength and quality of life (QoL) based on their most exacerbating tasks. Materials and methods: Seventy-five individuals with PFP completed open-ended questions about exacerbating tasks, AKPS, and KOOS-PF. Isometric hip abduction, hip extension, and knee extension strength were measured with a hand-held dynamometer while QoL was assessed with the KOOS-PF QoL subscale. Results: Sixty-five percent of individuals reported squatting in their top three most painful tasks, followed by running (49.33%), stair ambulation (40.00%), sitting (36.00%), jumping (30.67%), kneeling (28.00%), and walking (17.33%). AKPS does not assess kneeling, KOOS-PF does not assess stair ambulation or walking, and consensus statement does not evaluate walking or kneeling. There were non-significant differences in strength (p > 0.05); however, the stair ambulation group reported significantly worse QoL compared to the squatting (p < 0.001) and running (p = 0.015) groups. Conclusions: The AKPS, KOOS-PF, and consensus statement encapsulate most exacerbated tasks by individuals with PFP. Different exacerbating tasks may influence QoL, indicating a wide variety of functional tasks should be considered when developing tailored rehabilitation. Implications for rehabilitation: Frequently used patient-reported outcome measures encapsulate most, but not all, task-specific disabilities commonly reported by individuals with patellofemoral pain (PFP). Individuals with PFP who experience different pain provoking tasks do not present with differences in lower extremity isometric strength. Individuals with PFP who report stair ambulation as the most painful task have a worse quality of life compared to individuals who have pain with squatting or running. Rehabilitation professionals should consider identifying task-specific disabilities when developing a tailored rehabilitation program for individuals with PFP.